THE OCCURRENCE OF PRE MENSTRUAL SYNDROME BASED ON PHYSICAL ACTIVITIES AND NUTRITIONAL STATUS OF STUDENTS OF DIII KEBIDANAN BANGKALAN - Deasy Irawati; Novita Eka Kusuma Wardani; Fitriah Fitriah (Aloha International Journal of Health Advancement (AIJHA), 2019)
Menstruation is a natural occurrence and is commonly experienced by women. As a natural cycle, women certainly hope to undergo without physical or psychological disorders. However, some women experience Premenstrual Syndrome (PMS). Prevalence of premenstrual syndrome in female students in Surabaya is: 39.2% experienced severe symptoms and 60.8% experienced mild symptoms. 70% of students at DIII Kebidanan Bangkalan experience PMS symptoms. The aim of the study was to determine the correlation of physical activity and nutritional status to the incidence of PMS. Research design employed observational analysis with cross sectional approach. The population consisted of all the students of Year 1,2 and 3 at DIII Kebidanan Bangkalan. The sample, proportional simple random sampling technique was 119 students. . Independent variables were physical activity and nutritional status and dependent variable was incidence of PMS. Data collection used questionnaires, stature meters and scales. Data analysis technique used Rank Sperman test Statistical tests show a positive correlation between physical activity and PMS, positive correlation between nutritional status and PMS. The milder the physical activity, the tendency for PMS gets milder. The heavier the nutritional status the tendency for PMS gets heavier. Recent findings: PMS is not always influenced by physical activity factors. There is a correlation between physical activity and nutritional status and PMS for the students of DIII Kebidanan Bangkalan. It is hoped that there will be more pleasant social interaction among students so that they feel there is excitement and they create a balanced menu so that the nutritional status of students is maintained